Phytase dosing affects phytate degradation and Muc2 transporter gene expression in broiler starters - Kolapo M. Ajuwon; Vera Sommerfeld; Vicky Paul; Michael Däuber; Margit Schollenberger; Imke Kühn; Olayiwola Adeola; Markus Rodehutscord (Poultry Science, 2020)
This study was conducted to determine effects of high phytase use on growth performance, amino acid (AA) digestibility, intestinal phytate breakdown, and nutrient transporter expression in starter broiler chickens. Male Ross 308 chicks were allocated to 24 pens, at 15 birds/pen and assigned to one of 4 dietary treatments. Treatments were: a control diet (PCa+) that contained adequate levels of calcium (Ca) and phosphorus (P) for growing broiler chicks; a reduced Ca and P diet (PCa–:–1.5 g P/kg and –1.6 g Ca/kg), and 2 additional diets in which phytase was supplemented in the PCa– diet at 1,500 (PCa-Phy1500) and 3,000 (PCa-Phy3000) FTU/kg feed. A common starter diet was fed from day 1 to 8. From day 8 to 22, birds were fed the 4 experimental diets. On day 22, birds were killed for sample collection. From day 8 to 15, average daily gain and average daily feed intake were not different across treatments (P < 0.05) but gain-to-feed ratio (G:F) was reduced (P < 0.006) in the PCa– treatment compared with other treatments. There were no further performance differences, but a tendency of phytase treatments improving the overall G:F (P = 0.079; day 8–22). Up to both the duodenum–jejunum and ileum, phytate, P, and Ca disappearance were increased (P < 0.05) in the PCa-Phy1500 and PCa-Phy3000 treatments compared with PCa– treatment. Phytase dose dependently increased myoinositol (MI) concentration in the digesta from both the duodenum–jejunum and ileum (P < 0.001). The highest concentration of MI was found in the PCa-Phy3000 treatment. Plasma MI concentration was increased by phytase supplementation (P < 0.001). Prececal disappearance of Cys was lower (P < 0.05) in the PCa– treatment than in PCa1and PCa-Phy3000 treatment. Expression of MUC2 in the duodenum–jejunum was higher (P < 0.05) in the PCa-Phy3000 treatment than in other treatments. Phytase-induced hydrolysis of phytate led to elevated digesta and plasma MI concentrations and reduced digesta concentrations of phytate breakdown intermediates